Influence of Nozzle Material and Spray Parameters on Pure Aluminum and Aluminum 7075 coatings using Cold Gas Dynamic Spray - Leblanc Robert, Samuel (Université d'Ottawa / University of Ottawa, 2016)
Commercial airplanes are still using aluminum alloys as their primary structural material. Even if the used carbon fiber reinforced polymers is becoming more popular due to their extremely high strength to weight ratio, the majority of the existing flying fleet is still made out of aluminum alloys. This material was primarily used due to its high strength to weight ratio, ease to machine, excellent corrosion resistance properties and its high crash energy absorption. Aircraft components made of aluminum alloys are subjected to high stresses and harsh environments during flight, potentially leading them to crack and/or corrode. Presently, there is no industrial approved method to repair these components. Recycling damaged aircraft parts by repairing them would result in large cost savings for the industry. The present study was motivated by the potential use of the cold gas dynamic spray (CGDS) process to repair damaged aluminum 7075-T6 aircraft components. Two feedstock materials were used to repair this alloy in this research: pure aluminum and aluminum 7075. Pure aluminum is used in the aircraft industry on non-bearing components due to its extremely high corrosion resistance properties. Aluminum 7075 is the material of choice for structural applications due to its high strength. The results of this study show that CGDS could be potentially used to repair aluminum components on aircrafts. However, this research demonstrated that new commercially available equipments need to be further developed to successfully produce repaired components that meet the industry standards.